Fabrication egg white gel hydrolysates-stabilized oil-in-water emulsion and characterization of its stability and digestibility. (May 2020) - Ling, Ziting; Ai, Minmin; Zhou, Quan; Guo, Shanguang; Zhou, Ledan; Fan, Hong; Cao, Yuanyuan; Jiang, Aimin
Abstract: This paper investigated the properties of egg white protein hydrolysate (EH) prepared from alkali-induced egg white gel as an oil-in-water emulsion stabilizer. The physicochemical properties of EH, including Fourier transform infrared (FTIR), surface hydrophobicity, particle size, zeta potential and polydispersity index were investigated. Meanwhile, the microstructure, emulsion stability, oil oxidative stability, in vitro digestive stability and antioxidant activity of emulsion prepared by EH were evaluated. Results suggested that the surface hydrophobicity of EH decreased due to the destruction of hydrophobic groups, and the particle size of most hydrolysates ranged from 124.24 to 197.7 nm, except neutrase and alcalase hydrolysates. FTIR revealed that the strength of each peak increased significantly after hydrolysis owing to the break of structure and peptide bond. Most EH-stabilized emulsions were stable against droplets aggregation as influenced by temperature, and emulsion prepared from trypsin hydrolysate exhibited better ionic strength and storage stability. Emulsion stabilized by trypsin and alcalase hydrolysates delayed the lipids oxidation during storage. Droplet aggregation occurred to emulsions after in vitro digestion due to the destruction of the emulsion structure and the accumulation of proteins and lipids, and the release rate of free fatty acids ranged from 55.72% to 77.29% in the 2 h vitro intestine digestion for six different emulsions. Additionally, most digested EH-stabilized emulsion enhanced its ability to scavenge DPPH, ABTS and O 2− free radical, owing to the formation of antioxidant peptides. These results suggest that EH can be as a potential stabilizer for emulsions, especially trypsin hydrolysate, and possesses antioxidant properties after digestion. Graphical abstract: Image 1 Highlights: Egg white protein hydrolysates were prepared as oil-in-water emulsion stabilizer. Surface hydrophobicity of hydrolysates decreased obviously after hydrolyzed. EHAE and EHTE showed higher complex viscosity and loss modulus. EHT-prepared emulsion possessed stable ionic, temperature and storage stability. Antioxidant activities of emulsion were enhanced after in vitro digestion.